Dispositional need to belong and increased eating after social exclusion - Kaneko, Michihiro; Ueda, Yoshiyuki (Frontiers in Psychology, 2023)
Social exclusion affects the fundamental needs of individuals, and their coping behavior is moderated by their dispositional need to belong. Eating can be one such behavior. However, it is unclear how people with a higher or lower dispositional need to belong respond with respect to food consumption in response to social exclusion. Thus, this study aims to investigate which of these groups eat more food after social exclusion. Ninety-seven university students in Japan participated in two types of Cyberball games (where they either experienced social exclusion or social inclusion) in which their social exclusion status was manipulated. They subsequently participated in a test in which they ate as many cookies as they desired. Finally, they answered questions about their dispositional need to belong. Their BMI was also recorded. Results showed that when socially excluded, individuals with a low need to belong increased their consumption, while those with a high need to belong did not. We suggest that people with a lower need to belong are more inclined to focus on goals other than inclusion and instead use eating as a coping mechanism.